Low-protein diet decreased the adrenal function and spontaneous activity of mice during chronic heat stress. Issue 4 (April 2019) - Tsuda, Yuichi; Iwasawa, Kaori; Yamaguchi, Makoto
Abstract: Protein restriction is a well-known risk factor that induces the deterioration of various biological functions. However, little is known about the effects of protein restriction on behavioral markers and the adrenal function of mice exposed to chronic stress. Here we evaluated the effects of a low-protein diet on the spontaneous activity and adrenal function of chronic heat-stressed mice. ICR mice were fed a control diet (20% protein) or a low-protein diet (10% protein) for 14 consecutive days. From the 10th day of the diet period, the mice were repeatedly exposed to a temperature condition of 35 ± 1 °C for 2 hr/day for four consecutive days. The spontaneous activities of the mice were estimated for the behavioral analysis. On the last day, we performed a blood collection test and an ACTH stimulation test for adrenal function analysis. For the blood collection test, mice were exposed to heat stress again for 2 hr, and blood was collected immediately after this heat stress. We measured the plasma levels of corticotropin releasing hormone, adrenocorticotropin (ACTH), and corticosterone. For the ACTH stimulation test, cosyntropin was intraperitoneally administered, and the plasma corticosterone levels were measured. The spontaneous activity of the low-protein mice was significantly lower than that of the control mice during the dark period of heat stress. The plasma corticosterone levels were greatly increased by heat stress, with no significant difference between the control and low-protein groups. The ACTH stimulation test revealed that the plasma corticosterone concentration of the heat-stressed low-protein mice was significantly lower than that of the heat-stressed controls. In conclusion, the low-protein diet decreased the spontaneous activity and the adrenal function of mice during heat stress, which implies that protein restriction during chronic heat stress induces fatigue by reducing the adrenal function.